The Influence of Environtmental Disclosure, Hedging Policy, Capital Structure and Profitability on Firm Value - Florence Nightingale; Septian Afoan Gunawan; Zangiabadi (Journal of Accounting and Auditing, 2026)
Objective – This study aims to obtain empirical evidence on the Influence  of Environtmental Disclosure, Hedging Policy, and Capital Structure on Firm Value with Profitability as a moderation variable. Design/methodology/approach – This study uses a type of quantitative research. The sample in this study is 42 companies in the Non-Primary Consumer Goods sector listed on the Indonesia Stock Exchange in 2022-2024. The analysis technique used to test the hypothesis was logistic regression analysis using the Eviews 9 software. Findings – The results of the study show that Environtmental Disclosure has a negative effect on Firm Value. Meanwhile, the Hedging Policy has a negative effect on Firm Value. And Capital Structure has a negative effect on Firm Value. Then, Environtmental Disclosure weakens the influence  of Profitability on Firm Value. Meanwhile, the hedging policy strengthens the influence  of Profitability on Firm Value. Meanwhile, Capital Structure strengthens the influence of Profitability on Firm Value. Limitations/Implications of Research – The first limitation of this research is the type of data used in this study, namely secondary data obtained from the annual report published by the company. However, the data obtained is incomplete because many of the companies do not upload regularly every year. Furthermore, the content of the formula is incomplete or confusing, some numbers are not stated in the financial statements. Furthermore, this study has limitations in the sample from 166 to 42 samples, as for the rest due to incomplete financial statement data and many have suffered losses. And finally, the study was conducted over a specific period of time, namely 2022-2024, so it is not possible for a long-term analysis.